Maqashid al-Shariah and Cultural Ecology in the Green Economy: A Comparative Study of Islamic Sustainability Models in Indonesia and Malaysia - Harisah Harisah; Rahmat Dahlan; Zaenal Arief; Endang Darajat; Rahmawati-rahmawati (JURNAL ILMU SYARIAH, 2025)
In the face of the global environmental crisis and the inadequacies of purely technocratic sustainability models, Islamic ethical principles and local cultural values have emerged as vital resources for designing a holistic green economy. This study explores how maqāṣid al-sharīʿah (the higher objectives of Islamic law) interact with ecological cultural practices in shaping sustainability models in Indonesia and Malaysia, two Muslim-majority countries with distinct yet interconnected Islamic traditions and environmental challenges. Using a qualitative-comparative approach based on secondary data, official policy documents, and previous studies, this article examines various Islamic-based green initiatives, including eco-pesantren (eco-friendly Islamic boarding schools), environmental waqf projects, and green Islamic policies initiated by state religious institutions. The findings reveal that both countries integrate Islamic values into environmental practices through differing approaches: Indonesia emphasizes community-based environmental movements rooted in pesantren networks and local customs (adat), whereas Malaysia prioritizes institutional frameworks led by official authorities such as JAKIM. These models demonstrate that maqāṣid al-sharīʿah and cultural ecology function not only as normative frameworks but also as adaptive strategies shaping the ethical, spiritual, and practical dimensions of sustainable development. This study contributes to the discourse on Islamic sustainability by offering a value- and culture-based conceptual synthesis as an alternative to the dominant market-oriented economic paradigm. Keyword: Maqashid al-Shariah; Cultural Ecology; Green Economy